A dose-finding study on the effects of branch chain amino acids on surrogate markers of brain dopamine function. - Gijsman, H; Scarnà, A; Harmer, C; McTavish, S; Odontiadis, J; Cowen, P; Goodwin, G (2002)
RATIONALE: We have previously shown in healthy volunteers that an amino acid mixture lacking tyrosine and phenylalanine reduces tyrosine availability to the brain and produces cognitive and neuroendocrine effects consistent with reduced dopamine function. This could provide a potential nutritional approach to disorders such as mania and schizophrenia, which are characterised by overactivity of dopamine pathways. The amino acid mixture we tested previously is unpalatable, whereas mixtures containing only branch chain amino acids can be made more palatable. However, the effects of such mixtures on dopamine function in humans have not been studied. OBJECTIVE: To assess the tolerability of different doses of branch chain amino acids and to measure their effects on neuroendocrine and cognitive measures sensitive to changes in dopamine function. METHODS: We used a randomised, double-blind, cross-over design in 12 healthy volunteers to assess the effect of single oral doses of 10 g, 30 g and 60 g branch chain amino acids on plasma prolactin and a test of spatial recognition memory RESULTS: The branch chain amino acids were well tolerated. The availability of tyrosine for brain catecholamine synthesis decreased in a dose-related manner. As hypothesised, the drink increased both the plasma prolactin and the latency to respond on the spatial recognition memory task. CONCLUSIONS: A drink containing branch chain amino acids is well tolerated in healthy volunteers and produces effects consistent with lowered dopamine function.